Building strong foundations in C++: Scaffolded exercises with CodeRunner - Abd Aziz, Maslita; Shaarani, Ahmad Shaarizan; Kamal Baharin, Safiza Suhana; Othman, Zahriah; Hassan, Nor Hafeizah (2024)
Programming students often struggle with debugging and problem-solving due to limited feedback during learning. This study addresses these challenges by integrating CodeRunner, an automated assessment tool, with the PSIF framework to scaffold skill development. The objective was to enhance foundational, developmental, and mastery-level programming competencies. Through structured exercises on ULearn Moodle platform, students progressed from basic to advanced tasks, achieving significant improvements in success rates (e.g., 60% to 90% for complex exercises). CodeRunner’s real-time feedback and iterative approach enabled self-directed learning and error correction. This study highlights the potential of structured, feedback-driven learning to improve programming education outcomes effectively.